2016
DOI: 10.22364/eeb.14.10
|View full text |Cite
|
Sign up to set email alerts
|

The corollary effect of heavy metal accumulation in freshwater ponds on the hematological profile of Nile Tilapia (Oreochromis niloticus)

Abstract: The status of heavy metal buildup in commercial and non-commercial ponds of Nile tilapia (Oreochromis niloticus) and its effect on fish health was evaluated. Pond water and tilapia meat were examined for Pb, As, cadmium Cd and Cu using flame atomic absorption spectrometry; and Hg through manual cold-vapor atomic absorption spectrometry. Standard methods in hematology were applied to estimate red and white blood cell function of fish in relation to heavy metal accumulation. The results revealed significantly hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Similar results were observed in O. niloticus exposed to sub-lethal sodium selenite concentrations where leukocytosis was also associated to an increased lymphocyte, neutrophil, and monocyte counts (Ranzani-Paiva, Lombardi, Maiorino, Gonçalves, & Dias, 2014). The increase in cell types of the white series has been reported in other studies where fish were exposed to water contaminated with heavy metals, like in Anguilla anguilla exposed to water contaminated with lead (Santos & Hall, 1990), O. niloticus exposed to metals such copper, borium and lead in the aquatic environment (Garcia, Miguel, Gabriel, & Mingala, 2016), and Ctenopharyngodon idella exposure to copper and chromium (Shah et al, 2020).…”
Section: Discussionsupporting
confidence: 71%
“…Similar results were observed in O. niloticus exposed to sub-lethal sodium selenite concentrations where leukocytosis was also associated to an increased lymphocyte, neutrophil, and monocyte counts (Ranzani-Paiva, Lombardi, Maiorino, Gonçalves, & Dias, 2014). The increase in cell types of the white series has been reported in other studies where fish were exposed to water contaminated with heavy metals, like in Anguilla anguilla exposed to water contaminated with lead (Santos & Hall, 1990), O. niloticus exposed to metals such copper, borium and lead in the aquatic environment (Garcia, Miguel, Gabriel, & Mingala, 2016), and Ctenopharyngodon idella exposure to copper and chromium (Shah et al, 2020).…”
Section: Discussionsupporting
confidence: 71%
“…The presence of heavy metals in the waters and sediments of fish farms comes from many sources including agricultural activities (Garcia et al, 2016) and fish feed (Das et al, 2017). Many studies (Mostafa et al, 2015;Sarker et al, 2016;Adeyemi and Ugah, 2017;Maurya et al, 2018;Junejo et al, 2019) have demonstrated anthropogenic pollution of water and sediments in fish farms by heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…Growth performance is a factor reflecting environmental toxicity in fish, and even a small concentration of heavy metals has a negative effect, triggering physiological changes such as growth and metabolism and reducing health and survival rates (Hussain et al 2010). Hematological parameters are used to effectively monitor the status of fish exposed to various types of toxicity in the aquatic environment (Garcia et al 2016). The main goal of ecotoxicology in aquatic ecosystems is to assess the toxicity of aquatic organisms and humans (Ribeiro et al 2006).…”
Section: Introductionmentioning
confidence: 99%